Renal cyst evolution in childhood: a contemporary observational study. Issue 2 (April 2019) - Rediger, C.; Guerra, L.A.; Keays, M.A.; Wayne, C.; Reddy, D.; Ksara, S.; Leonard, M.P.
Summary: Introduction: Children with renal cysts often undergo ultrasound (US) monitoring to identify malignant transformation or polycystic kidney disease (PKD). However, the utility of ongoing surveillance is uncertain. Objective: The objective of this study was to assess the natural history of simple or minimally complex cysts and the proportion of progression to autosomal dominant polycystic kidney disease (ADPKD), autosomal recessive polycystic kidney disease (ARPKD), or malignancy. Study design: The institutional review board approved retrospective chart review at one institution between 2004 and 2014. Eligible patients had ≤3 simple or minimally complex cyst(s) discovered on US without an initial diagnosis of multicystic dysplastic kidney, genitourinary malignancy, ADPKD, or ARPKD. Patient demographics and cyst details were recorded at identification and follow-up visits. Logistic regression was used to examine univariate association between diagnosis of ADPKD/ARPKD and each recorded variable. Results: Eighty-seven eligible patients were identified. Twenty-two patients were identified antenatally or in the first year of life; the remaining 65 were identified at >1 year of age, median 7.6 years (interquartile range [IQR]: 4.2, 10.6). Most (60/87, 69%) had a solitary cyst at initial US. The median length of follow-up was 4.1 years (IQR: 1.9, 6.8) with median 3 follow-up US (IQR: 2, 5). Eleven patients (12.6%) were diagnosed with ADPKD. One patient (1.2%) was diagnosed with ARPKD. A median 2 follow-up US (IQR: 1, 4) procedures were performed over a median of 2.2 years (IQR: 1.0, 3.9) to obtain diagnoses of ADPKD or ARPKD. No patients developed malignancy. Discussion: This study's results reveal that children identified to have a small number of simple or minimally complex renal cysts on initial US are unlikely to require additional treatment for these cysts as transformation to PKD or malignant condition is rare. Supporting this are results from literature that although simple cysts in childhood may evolve over time, most do not require any surgical or invasive treatment in the long term. Limitations include retrospective design and single institution. Conclusions: Autosomal dominant polycystic kidney disease/autosomal recessive polycystic kidney disease diagnosis occurs early in follow-up evaluation in children with simple or minimally complex cysts. Malignant transformation did not occur in any patients in this study. Patient summary: This study examines the natural history of renal cysts in childhood. Following up simple renal cysts routinely beyond 2–3 years after initial detection may not be optimal due to the use of limited medical resources. Summary Table Summary of final diagnoses Summary Table Final diagnosis a n (%); (95% CI) ADPKD 11 (12.6) (7.2–21.2) ARPKD 1 (1.1) (0.2–6.2) Minimally complex cyst 5 (5.7) (2.5–12.8) Renal dysplasia 1 (1.1) (0.2–6.2) Simple cyst 1 (1.1) (0.2–6.2) Renal cyst NOS b 75 (86.2) (77.4–91.9) Resolution 10 (11.5) (6.4–19.9) Malignancy 0 (0) (0–4.2) ADPKD = autosomal dominant polycystic kidney disease; ARPKD = autosomal recessive polycystic kidney disease; NOS = not otherwise specified. a Multiple diagnoses possible. b Not otherwise specified.